Geoquímica deposicional de metais e hidrocarbonetos no estuário do canal da Passagem (Vitória-ES) e no sistema esuarino dos rios Piraquê-Açú e Piraquê-Mirim (Aracruz-ES) - Costa, Eduardo Schettini (2014)
The sediment cores study can provide a historical record of several influences for deposition of pollutants on the aquatic system. As a way to evaluate the natural or anthropogenic deposition of metals and hydrocarbons in two important estuaries of the Espírito Santo, this study examined the levels of these in three sediment cores (P1 , P2 and P3) of the Passagem Channel estuary and three sediment cores (PA05 , 9bnorte and PM01) of the Piraquê-Açú and Piraquê-Mirim Estuarine System (PAPMES). Geochemical markers (d 13C e d 15N stale isotopes and Corg./Ntotal ratio), grain size, carbonate content and sedimentation rate (Passage Channel estuary only) were also analyzed. The results showed an anthropogenic contribution to metals (Zn, Cd, Cu and Pb), which does not happen in the PAPMES, even with higher concentrations of these metals. This difference is possibly due to high input of these elements from Barreiras Formation to the PAPMES. Arsenic in SEPAPM has a high concentration compared with others estuaries, possibly due to an input from the Barreiras Formation and to the deposition associated with the calcium carbonate and Fe/Mn oxyhydroxides. The organic content also presents different rules between the estuaries, being directly relate with metallic elements deposition, especially when associated with petrogenic compounds and domestic effluents derivatives. This pattern does not occur in PAPMES, where the organic content is not directly associated with metals. These contaminations by metals and hydrocarbons in the Passagem Channel are possibly associated to activities that use oil or its derivatives (mooring small boats) and runoff containing waste tires, fuels, lubricants and brake pads. In addition, there is also the increase of the disposal of domestic sewage related to the high population growth in the region of the Great Vitoria. The Piraquê-Açú and Piraquê-Mirim Estuarine System showed no indication of anthropogenic enrichment of metals and petrogenic hydrocarbons contamination.